Politics of security : British and West German protest movements and the early Cold War, 1945-1970 - Nehring, Holger, 1974- (Oxford : Oxford University Press, 2014)
Focuses on a number of peace movements in Britain and West Germany from the end of Second World War in 1945 to the early 1970s to understand how European societies experienced and reacted to the Cold War.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 5, 2013).
Keywords: Protest movements -- Great Britain -- History -- 20th century; Protest movements -- Germany (West) -- History -- 20th century; Cold War